Adolescence and pelvic inflammatory disease: diagnostic and therapeutic challenges in pediatric practice (Archives of Pediatrics of Uruguay, 2026)
Introduction: Pelvic Inflammatory Disease (PID) is an infection of the upper genital tract that can affect the uterus, fallopian tubes, or ovaries. Adolescence is a recognized risk factor for its development. It is most often secondary to a sexually transmitted infection (STI). The most frequently involved germs are: Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG). Its diagnosis requires a high level of suspicion. It is based on the presence of pelvic pain or leukorrhea, fever, leukocytes, and the characteristic germ in the vaginal exudate. The risk of acute and/or chronic complications is high; early antibiotic treatment is essential to prevent them.Objectives: to describe the comprehensive management of an adolescent with pelvic pain secondary to PID treated at a public pediatric reference hospital in Uruguay.Clinical Case: 14-year-old female. Began sexual intercourse at age 13, with multiple sexual partners. Irregular use of barrier methods. Presented with 5 days of hypogastric abdominal pain, nausea, and vomiting. Mucopurulent leukorrhea, without odor or itching. After 72 hours, her axillary temperature rose up to 39 degrees. No other symptoms. Physical Examination: Flat abdomen, tense in the hypogastrium, diffuse pain on superficial and deep compression. No guarding or contracture.Genital Examination: Vulva and vagina without lesions. Macroscopically healthy cervix. Whitish leukorrhea, non-odorous. On vaginal touch, the cervix was posterior, 2 centimeters long, closed. Uterus in anteversion-flexion, no pain on bimanual palpation. No cervical motion tenderness. Douglas’ pouch free and non-tender. Laboratory Findings: White blood cells 15,000/L, Neutrophils 10,000/L, C-reactive protein 156mg/dL. Vaginal Exudate: NG positive. Negative for CT and Trichomonas. She received non-steroidal anti-inflammatory drugs, ceftriaxone, metronidazole, and doxycycline intravenously for 14 days.Conclusions: pelvic pain is a frequent reason for consultation in adolescence, and the healthcare team must be familiar with its management. PID is one of its possible causes. It is important to maintain a high level of suspicion in the presence of risk factors and leukorrhea associated with pelvic pain. The diagnosis is fundamentally clinical with microbiological confirmation. Early antibiotic therapy is essential to prevent short- and long-term complications.
Keywords: Pelvic Inflammatory Disease; Adolescent; Pelvic pain